PENGEMBANGAN POP-UP BOOK BERBANTUAN PENERAPAN MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN DIMENSI KREATIF PESERTA DIDIK - Lihardo Hulu, Irwan; Huda, M. Komarul; Saragih, Ester (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2024)
This study aims to determine whether pop-up book media assisted by the application of the project-based earning model can be said to be feasible as a learning medium and to determine the increase in the creative dimension of students. This research uses ADDIE development research design and classroom action research (PTK). The results of this study showed a percentage of 86% for media experts who could be categorized as very feasible, 92% for material experts who could be categorized as very feasible, 91% for student responses who were included in the very feasible category. The results of this study also show that there is an increase in the creative dimension of students which can be seen from the acquisition of data in cycle I and cycle II. In cycle I there were 8 students who had criteria to develop according to expectations with a percentage of 32%, then in cycle II as many as 24 students who had criteria to develop very well with a percentage of 96%. So it can be concluded that the media developed in the form of pop-up book media assisted by the project based learning model can be said to be feasible as a learning medium and can increase the creative dimension of students.